GEOGRAPHICAL CLASSIFICATION OF VIETNAMESE DRAGON FRUIT (Hylocereus spp.) USING ICP-MS AND PCA - Quang Minh Bui; Ha Minh Duc Tran; Ngoc Minh Truong; Viet Anh Le; Thi Quynh Bui; Hoang Khanh Nguyen; Quang Hai Vu; Van Nhan Le (Journal of Animal and Plant Sciences, 2025)
A geographical classification is a systematic framework for organizing and categorizing location-based data, facilitating the comparative analysis and interpretation of spatial distributions and regional characteristics. This study investigates the elemental composition and nutritional profiles of dragon fruits (Hylocereus spp.) collected from four major cultivation provinces in Vietnam: Tien Giang, Vinh Long, Long An, and Binh Thuan, using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and Principal Component Analysis (PCA). A total of 80 samples (20 per province) were analyzed, revealing significant regional differences in elemental concentrations. Notably, Binh Thuan samples exhibited the highest levels of Nickel (34.09±1.98 µg/g), Chromium (86.11±4.16 µg/g), and Iron (3.08±0.21 µg/g), reflecting unique soil characteristics. Nutritional assessments indicated that Tien Giang samples had the highest Vitamin C content (30.65±0.16 mg/100 g) and acidity (5.80±0.40 mg/100 g). The PCA demonstrated clear clustering of samples by region, with elements such as Manganese, Yttrium, Barium, Potassium, Titanium, Sodium, Arsenic, and Cadmium contributing most to classification. Protein, lipid, and total sugar levels showed minimal variation across regions. These results highlight ICP-MS and PCA as effective tools for geographic traceability and quality control of agricultural products, supporting Vietnam's dragon fruit industry in meeting global export standards. Future applications include integrating traceability systems to enhance product authenticity and safety in international markets.
Keywords: dragon fruit; geographical classification; ICP-MS; Principal Component Analysis